WOMEN’S ECONOMIC INCLUSION – A CALL FOR COLLECTIVE EFFORTS - Roosalina Wulandari (Journal of Business Strategy and Execution, 2018)
Being half of the population, there is no doubt that women significantly contribute to civilization. For centuries, men and women have been complementary to each other as we try to fulfill the expected gender roles constructed and assigned by the community. In many cultures, patriarchy has been the one dominant ideology that has shaped how the community perceived and constructed stereotyped gender roles, to the extent that this gender role covers areas that should have been equally shared by both genders. As men thrived to be leaders of the pack, designed with masculine themes and expected to be the protectors of women, the other gender has been living with a prescription of domestic values with less powerful attributes.This imbalanced role then translated into many areas of social function, and was disadvantageous to women. In a strongly incorporated patriarchal culture, women struggled to be able to break the perceived glass ceilings that were defined by patriarchy and believed in by both genders.This paper focuses on how the gender role plays part in women’s capacity to contribute in the economic growth, one of the areas that is traditionally not assigned to the gender role and yet has experienced shifting. This paper will employ a literature review approach to examine the contributing factors that promote or hinder women’s economic inclusion. The review echoes findings on how patriarchy, education and government policies play an important part to ensure the sustainability of women’s economic inclusion. To conclude, some recommendations are provided on how policies should be reviewed to address existing women’s economic contribution, both in the labor force and in care-work in the household.